Evaluation of the Implementation of the Sekolah Penggerak Program Using the CIPP Model in Middle Schools in East Manggarai Regency - Marianus Tapung; Marselus Ruben Payong; Alfonsus Sam (Eduvest - Journal of Universal Studies, 2024)
This study is an evaluation of the implementation of the School Mover program in 23 junior high schools in East Manggarai Regency using the Context, Input, Process, and Product (CIPP) model. This study aims to analyze the Context, Input, Process, and Product of the program. The method used in this research is descriptive statistics to measure the perceptions and evaluations of school principals, teachers, school supervisors, facilitators, school committees and stakeholders. The results of statistical measurements of perceptions and evaluations were juxtaposed with data from interviews and document reviews. The results of the data analysis show that the Input, Process and Product aspects fall into the "Good" level, while the Context aspect falls into the "Weak/Lacking" category. Weakness or lack of context aspect is caused by many factors, among others, the lack of involvement of local communities and accommodating socio-cultural needs in the planning and implementation of the Mobilizing School Program. For this reason, schools need to conduct an in-depth analysis of the contextual factors that influence the implementation of the program, such as the socioeconomic conditions of the community, local culture, education infrastructure and local government policies. Schools need to consider the active involvement of all stakeholders, including local government, schools, teachers, parents and local communities, in formulating and implementing strategies to strengthen the context aspect.